Influence of Metal Dopant (Cu, Co, Sm, Sn) on Ni/ScSZ Thin Film Anode in Solid Oxide Fuel Cell - Nor Anisa Arifin; Abdullah A Afifi; Navina Kumar; Nur Natasha Roslan; Andanastuti Muchtar (IDRIS Darulfunun Institute, 2024)
Solid oxide fuel cells (SOFCs) are highly efficient electrochemical conversion devices that generates electrical energy through electrochemical reaction of gaseous fuel. Doping on the SOFC anode catalyst has the potential to increase the performance and tolerance of SOFC towards hydrocarbon fuel. An understanding of the doping effect of different type of catalyst on the SOFC anode is essential due to the differences in the characteristics of the catalysts and the impact on the existing anode catalyst microstructure with the dopant addition. This study is aimed to identify the effect of metal catalysts doping on the microstructure and electrochemical performance of Ni/ScSZ thin composite anodes on the SOFC electrolyte supported cell with surface infiltration method. The impact on the anode catalyst’s microstructure, distribution of element and elemental analysis was carried out using SEM-EDX and XRD analysis. The electrochemical performance of the cells were evaluated by the maximum power density and open-circuit-voltage (OCV) from the current-voltage (iV) measurement in hydrogen and in biogas. The results of this study found that the presence of dopant introduction of 5wt% dopant/Ni can be detected by EDX, but not with lower concentration. For Sn, Sm and Cu doped cells, the XRD analysis detected Ni3Sn, Ni2Sm and Cu0.81Ni0.19 alloy formed, respectively. Doping by 0.5 wt% of Sn/Ni and 5wt% of Sm/Ni improved the electrochemical performance in hydrogen by three-fold and two-fold (184mW/cm2 and 100mW/cm2, respectively) compared to 49 mW/cm2 in the undoped cell. Addition of Cu showed the best tolerance with biogas operation. Co addition on the other hand posed a negative impact and the microstructure of the anode become overly dense. This work observed different impact dopant by various dopant on the cell’s porosity which influenced the electrochemical reaction. As the result with biogas deviates from previous investigation with anode supported cell, it can be concluded that for electrolyte supported cell with thin anode which have limited catalytic area as the reforming reaction reaction compete with the triple phase boundary area for electrochemical reaction.